Primary central nervous system gamma delta cytotoxic T-cell lymphoma. (April 2016) - Mooney, Kelly L.; Choy, Winward; Woodard, Joslyn; Xian, Rena R.; Deal, Taylor M.; Kendle, Ryan F.; Said, Jonathan; Grody, Wayne; Yang, Isaac
Highlights: This is the first report of primary CNS gamma/delta cytotoxic T-cell lymphoma. Only nine cases of CD8+ T-cell lymphoma of the CNS have been reported. Median age is 45 years, with 66% males and 66% Korean ethnicity. Data on outcomes is limited, with 4/9 deaths in reported cases. Diagnosis relies on CD8 positivity with concurrent stains (granzyme B, perforin). Therapy includes surgery, radiotherapy, chemotherapy, or autologous stem-cell based treatments. Abstract: Primary T-cell lymphomas of the central nervous system (CNS) are uncommon, but aggressive and increasing in incidence. We describe a rare case of T-cell lymphoma in a cerebellar location, to our knowledge the first reported case demonstrating gamma/delta receptor expression. Additionally, we elaborate on key diagnostic features and review all nine patients with primary CNS lymphoma of cytotoxic T-cell phenotype reported in the literature. A 26-year-old female medical student presented with a 6 week history of nausea, vomiting and dizziness. MRI revealed a 2 cm cerebellar mass. The tumor was subtotally resected, and pathologic examination of a subtotal resection specimen demonstrated peripheral T-cell lymphoma, not otherwise specified, with a gamma/delta cytotoxic T-cell phenotype. She subsequently started high dose methotrexate and cytarabine. We report a unique case of primary CNS gamma delta CD8+ T-cell lymphoma lineage in a young female patient. While these are rare entities, it is an important differential diagnosis to consider. Therapy should be tailored to the patient, and involves resection with adjuvant chemotherapy, radiotherapy or autologous stem-cell based treatments.